STUDI PENGARUH WAKTU TRANSESTERIFIKASI PADA SINTESIS BIODIESEL DARI BIJI KARET DENGAN MENGGUNAKAN KATALIS CaO/ZnO/y-Al2O3 - Ida Hasmita; Chartika Putri; Zulhaini Sartika; Khairul Akli (REACTOR: Journal of Research on Chemistry and Engineering, 2026)
Rubber seeds (Hevea brasiliensis) from Aceh plantations, Indonesia, offer a promising non-edible feedstock for biodiesel synthesis via transesterification due to their high oil content addressing fossil fuel depletion and environmental challenges. This study examines the effect of transesterification time on biodiesel yield and quality using a novel CaO-ZnO/γ-Al₂O₃ heterogeneous catalyst. Rubber seed oil was extracted via Soxhlet method with n-hexane, degummed with phosphoric acid, and transesterified with methanol (1:15 molar ratio, 3 wt% catalyst) at 70°C for 60, 70, and 80 minutes. Oil characterization revealed low moisture (0.012%) and free fatty acids (7.96%). Maximum yield reached 95% at 70 minutes, attributed to optimal triglyceride-methanol interactions before saturation. Density values (903.5-941.5 kg/m³) exceeded SNI 7182:2015 limits (≤860 kg/m³) due to incomplete glycerol separation, while kinematic viscosity met standards (2.67-2.88 mm²/s). GC-MS of the optimal sample identified key fatty acid methyl esters: octadeca-9,12-dienoic acid (33.13%), oleic acid (3.37%), linoleic acid (2.40%), and hexadecenoic acid (1.04%). These results confirm rubber seed biodiesel viability with process optimization needed for density compliance, promoting waste valorization in rubber-producing regions.